2010
DOI: 10.1074/jbc.m109.087445
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Relocalization of the Endoplasmic Reticulum Chaperone and Unfolded Protein Response Regulator GRP78/BiP

Abstract: The recent discovery that GRP78/BiP, a typical endoplasmic reticulum (ER) lumenal chaperone, can be expressed on the cell surface, interacting with an increasing repertoire of surface proteins and acting as receptor in signaling pathways, represents a paradigm shift in its biological function. However, the mechanism of GRP78 trafficking from the ER to the cell surface is not well understood. Using a combination of cellular, biochemical, and mutational approaches, we tested multiple hypotheses. Here we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
272
2
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(304 citation statements)
references
References 39 publications
17
272
2
8
Order By: Relevance
“…20,22 Overexpression of GRP78 triggers the re-localization of GRP78 to cell surface and is associated with advanced stages of tumor progression and invasiveness. 8,23 Thus, we investigated the relationship between levels of cell-surface GRP78 and susceptibility of cells to ISM-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…20,22 Overexpression of GRP78 triggers the re-localization of GRP78 to cell surface and is associated with advanced stages of tumor progression and invasiveness. 8,23 Thus, we investigated the relationship between levels of cell-surface GRP78 and susceptibility of cells to ISM-induced apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies using transmembrane prediction programs have suggested that GRP78 has four potential transmembrane domains at the cell surface: I (amino acids (aa) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], II (aa 29 -45), III (aa 222-242), and IV (aa 414 -431) (34). However, the studies performed here demonstrate that at least residues 416 -417 are exposed on the cell surface, as this is the sole SubA cleavage site, and we observe cell-surface cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was discovered that ER stress can actively promote cell-surface localization of GRP78 (15), where it assumes coreceptor functions with cell-surface protein partners in regulating signal transduction pathways, including PI3K/AKT/S6 activation (16)(17)(18)(19). Although homozygous knockout of Grp78 results in embryonic lethality, heterozygous Grp78 mice expressing an ∼50% level of GRP78 are viable and phenotypically normal (20).…”
mentioning
confidence: 99%